Low cytotoxic elastic niosomes loaded with salmon calcitonin on human skin fibroblasts - Aranya Manosroi (2018)
A low cytotoxic elastic niosomal formulation loaded with salmon calcitonin was developed. The elastic niosomes were prepared from Tween 61 mixed with cholesterol at various concentrations of the edge activators (sodium cholate (NaC) and sodium deoxycholate (NaDC); 0.25, 0.5, 2.5, 5 and 10% mole) or ethanol (10-30% v/v). The effects of the niosomal concentrations (5, 10 and 20 mM) and phosphate buffer at pH 7.0 (5, 10, 20 and 30 mM) on the physical characteristics of niosomes were investigated. The 5 mM elastic niosomes in 5 mM phosphate buffer containing calcitonin 0.22 mg/mL gave the highest elasticity (deformability index (DI)) at 6.79 ± 2.03 determined by the extrusion method. The blank elastic niosomes comprised 2.5% mole NaDC, 5% mole NaC or 20% v/v ethanol showed the highest elasticity. The 5% mole NaC elastic niosomes loaded with calcitonin gave the highest DI (21.59 ± 0.91) and percentages of calcitonin entrapment efficiency (60.11 ± 4.98). This study has demonstrated that this NaC elastic niosome did not only reduce the cytotoxicity of the loaded calcitonin but also gave superior cell viability to the ethanolic elastic niosome as well. © The Author(s) 2013.